Efficient Hybrid Amorphous Silicon/Organic Tandem Solar Cells Enabled by Near‐Infrared Absorbing Nonfullerene Acceptors. Issue 23 (30th April 2021) - Troughton, Joel; Neubert, Sebastian; Gasparini, Nicola; Villalva, Diego Rosas; Bertrandie, Jules; Seitkhan, Akmaral; Paleti, Sri Harish Kumar; Sharma, Anirudh; De Bastiani, Michele; Aydin, Erkan; Anthopoulos, Thomas D.; De Wolf, Stefaan; et al.
Abstract: Monolithically stacked tandem solar cells present opportunities to absorb more of the sun's radiation while reducing the degree of energetic loss through thermalization. In these applications, the bandgap of the tandem's constituent subcells must be carefully adjusted so as to avoid competition for photons. Organic photovoltaics based on nonfullerene acceptors (NFAs) have recently exploded in popularity owing to the ease with which their electrical and optical properties can be tuned through chemistry. Here, highly complementary and efficient 2‐terminal tandem solar cells are reported based on a wide bandgap amorphous silicon absorber, and a narrow bandgap NFA bulk‐heterojunction with power conversion efficiencies (PCEs) exceeding 15%. Interface engineering of this tandem device allows for high PCEs across a wide range of light intensities both above and below "1 sun." Furthermore, the addition of an inorganic silicon subcell enhances the operational stability of the tandem by reducing the light‐stress experienced by the bulk heterojunction, resolving a long‐standing stumbling block in organic photovoltaic research. Abstract : In this work, tandem solar cells using wide bandgap hydrogenated amorphous silicon and narrow bandgap organic bulk heterojunction photovoltaics are explored. By chemically texturing transparent conductive oxide layers, the current matching between two subcells can be optimized to give a power‐conversion efficiency of 15% while greatly improving operational stability compared to single junction organic photovoltaics.